TCF/LEF Transcription Factors: An Update from the Internet Resources - Hrckulak, Dusan; Kolar, Michal; Strnad, Hynek; Korinek, Vladimir (Cancers, 2016)
T-cell factor/lymphoid enhancer-binding factor (TCF/LEF) proteins (TCFs) from the High Mobility Group (HMG) box family act as the main downstream effectors of the Wnt signaling pathway. The mammalian TCF/LEF family comprises four nuclear factors designated TCF7, LEF1, TCF7L1, and TCF7L2 (also known as TCF1, LEF1, TCF3, and TCF4, respectively). The proteins display common structural features and are often expressed in overlapping patterns implying their redundancy. Such redundancy was indeed observed in gene targeting studies; however, individual family members also exhibit unique features that are not recapitulated by the related proteins. In the present viewpoint, we summarized our current knowledge about the specific features of individual TCFs, namely structural-functional studies, posttranslational modifications, interacting partners, and phenotypes obtained upon gene targeting in the mouse. In addition, we employed several publicly available databases and web tools to evaluate the expression patterns and production of gene-specific isoforms of the TCF/LEF family members in human cells and tissues.
Keywords: Fantom5; the Cancer Genome Atlas; Wnt signaling; GTEx; splicing isoforms